Tingkat Pengetahuan Siswa Kelas Viii B Smp Negeri 7 Satarmese Tentang Peraturan Dan Teknik Dasar Permainan Sepak Bola - Segi, Longginus; Ramli, Astuti Cendrawati; Tonda, Hironimus (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
To date, there has been no research specifically examining the level of knowledge of class VIII B students at SMP Negeri 7 Satarmese regarding soccer rules. This school also provides Physical Education (PE) lessons with soccer material, so it is important to determine the extent to which students understand the rules of the game. This study uses a quantitative approach with descriptive methods. The descriptive research design was chosen because this study aims to describe the level of knowledge of class VIII B students at SMP Negeri 7 Satarmese regarding the rules and basic techniques of soccer as they are, without providing any treatment or variable manipulation. In terms of soccer rules, the results show that the average score obtained by students was 56.19 with a standard deviation of 9.32. This figure indicates that the level of distribution of scores among students is relatively moderate. In terms of basic soccer techniques, the results show an average score of 56.21 with a standard deviation of 15.88. This value indicates that students' knowledge of basic techniques is still in the sufficient to good category.